Integrating Buddhist Principles Into Management Control Systems: A Cattari Ariya Saccani Approach - Irma Cahyani Kawi; Wiyono Pontjoharyo (Pandawan, 2023)
An organization or business entity has multiple goals, including providing happiness to stakeholders, fostering harmony with the surrounding environment and nature, and instilling universal, transcendental values in each member. The role of each individual in an organization or business entity is crucial as they are the source of human power. Therefore, self-control is an important aspect that must be addressed. According to various studies, organizations or business entities that incorporate spirituality in their activities have proven to be sustainable and successful. The Management Control System (MCS) can play a role in achieving this.Â Â This study adopts a qualitative, exploratory research approach to gain a deeper understanding of the essence of the MCS based on the Cattari Ariya Saccani approach. which is not well known to the public and could lead to the creation of a new conceptual model. Cattari Ariya Saccani is a Buddhist teaching that integrates self-control with noble values and spiritual dimensions, different from the general MCS, making it suitable for exploring its unique essence. This study aims to contribute to existing theory by providing insights into the Cattari Ariya Saccani approach to MCS, which balances material, rational, and formal aspects of MCS with spiritual and ethical considerations. This research contributes to the literature by advancing the understanding of integrating religious principles into the business and management context. The practical implications suggest that organizations could consider adopting Buddhist principles through the Cattari Ariya Saccani approach as a means to enhance wisdom and ethical decision-making, as well as to promote sustainability in their operations.